2019
DOI: 10.17221/202/2017-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, antimicrobial and insecticidal activities of the tunisian Citrus aurantium essential oils

Abstract: The chemical composition of volatile fractions from leaves, flowers and peels of Citrus aurantium growing in Tunisia obtained by hydrodistillation were analysed using GC and GC-MS. Furthermore, the isolated essential oils were evaluated for their in vitro antimicrobial activity against eight bacteria, eight phytopathogenic and nine human pathogenic fungi. The essential oils from peels and its main compound limonene have been found to possess strong contact toxicity against four storage-grain insects. The highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 46 publications
3
21
1
Order By: Relevance
“…Chen et al [113] determined the antibacterial activity of C. maxima EO against human pathogenic bacteria (E. coli, B. subtilis, S. aureus, P. aeruginosa, B. licheniformis, and B. altitudinis) using minimum inhibition concentration (MIC) ranging from 475-1104 µg/mL, where the EO showed inhibition against all the strains. Further, the antibacterial activity of EO from C. aurantium against eight pathogenic bacteria (S. epidermidis, P. aeruginosa, S. aureus, M. luteus, E. coli, S. typhimerium, L. monocytogenese, and E. faecium) showed maximum inhibition zone ranging from 6-16 mm for all the strains at a concentration of 7 µL per disc [114]. Similarly, the peel EO of Citrus reticulata, Citrus sinensis, and Citrus × sinensis were subjected for antibacterial analysis against four pathogenic bacteria, two Gram +ve (S. aureus and B. subtilis) and two Gram −ve bacteria (E. coli and P. multocida), using disc diffusion assay.…”
Section: Ceo As An Antibacterial Agentmentioning
confidence: 97%
“…Chen et al [113] determined the antibacterial activity of C. maxima EO against human pathogenic bacteria (E. coli, B. subtilis, S. aureus, P. aeruginosa, B. licheniformis, and B. altitudinis) using minimum inhibition concentration (MIC) ranging from 475-1104 µg/mL, where the EO showed inhibition against all the strains. Further, the antibacterial activity of EO from C. aurantium against eight pathogenic bacteria (S. epidermidis, P. aeruginosa, S. aureus, M. luteus, E. coli, S. typhimerium, L. monocytogenese, and E. faecium) showed maximum inhibition zone ranging from 6-16 mm for all the strains at a concentration of 7 µL per disc [114]. Similarly, the peel EO of Citrus reticulata, Citrus sinensis, and Citrus × sinensis were subjected for antibacterial analysis against four pathogenic bacteria, two Gram +ve (S. aureus and B. subtilis) and two Gram −ve bacteria (E. coli and P. multocida), using disc diffusion assay.…”
Section: Ceo As An Antibacterial Agentmentioning
confidence: 97%
“…In continuation of our research to discover potential natural therapeutic agents [24][25][26][27][28][29][30][31][32][33], this study aimed to investigate the composition of C. carvi and C. sativum EOs by GC-MS analysis. To elucidate their pharmacotherapeutic virtues, we assessed their antioxidant and antimicrobial activities, and we reported for the first time their anti-acetylcholinesterase and antidiabetic inhibitory effect alone and in combination.…”
Section: Introductionmentioning
confidence: 99%
“…limonene, terpinene, o-cymene, β-caryophyllene against Tribolium castaneum and recorded γ-terpinene as the most effective insecticidal compound having LC50 value of 4.1 mg/l air and β-caryophyllene as the effective repellent compound. Limonene was reported to have almost similar fumigant toxicity like that of crude EO of C. aurantium against Tribolium castaneum, Sitophilus granarium and Cryptolestes ferrugineus [28]. In our earlier studies we found higher toxicity of citral, that is the major compound of the essential oil of Citrus aurantifolia than the crude oil as mosquito larvicidal, ovicidal and adulticidal against Aedes aegypti [23].…”
Section: Citrus Eo Compounds Against Insect Spmentioning
confidence: 61%
“…From Tunisian Citrus aurantium, limonene percentage in leaves, flowers and peel EOs were 6.52, 5.03, 73.6% respectively, linalool occupied 37.24, 41.82, 4.8% respectively, linaly acetate occupied 7.87, 13.75, 1.6% respectively and neral share was almost of similar (3.40, 4.80, 3.26% respectively) percentage. β-pinene composition for leaves and flowers were 9.68 and 9.21% respectively and α-thujene composition were 10.65 and 6.15% respectively but both β-pinene and α-thujene present below 0.5% in peel EO of the plant [28].…”
Section: Citrus Aurantiummentioning
confidence: 89%
See 1 more Smart Citation